2008
DOI: 10.1002/jssc.200800021
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of polyphenols with potential antioxidant properties in wines using reverse phase HPLC

Abstract: A RP-HPLC method with photodiode array detection (DAD) was developed to separate, identify and quantify simultaneously the most representative phenolic compounds present in Madeira and Canary Islands wines. The optimized chromatographic method was carefully validated in terms of linearity, precision, accuracy and sensitivity. A high repeatability and a good stability of phenolics retention times (a 3%) were obtained, as well as relative peak area. Also high recoveries were achieved, over 80.3%. Polyphenols cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
30
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 33 publications
12
30
2
Order By: Relevance
“…As it can be seen in Table 1, the MEPS C8 /ULPC-PDA methodology gave very low LODs (0.21 mg/mL) and LOQs (0.68 mg/mL). These limits are comparable with those obtained by other authors [44][45][46]48]. Table 1) and (B) influence of MEPS sorbents on (E)-resveratrol extraction efficiency (error bars represent standard error of the mean (n 5 3) for each data point).…”
Section: Methods Validationsupporting
confidence: 89%
See 1 more Smart Citation
“…As it can be seen in Table 1, the MEPS C8 /ULPC-PDA methodology gave very low LODs (0.21 mg/mL) and LOQs (0.68 mg/mL). These limits are comparable with those obtained by other authors [44][45][46]48]. Table 1) and (B) influence of MEPS sorbents on (E)-resveratrol extraction efficiency (error bars represent standard error of the mean (n 5 3) for each data point).…”
Section: Methods Validationsupporting
confidence: 89%
“…Quantitative analysis of (E)-resveratrol is commonly performed by means of high-performance liquid chromatography (HPLC) connected to a diode array detector or a triple quadrupole mass spectrometer [26,27,[41][42][43][44][45][46][47][48]. In order to increase the selectivity and sensibility of the analytical method the analysis of these kinds of compounds should be performed by using a fluorescence detector.…”
mentioning
confidence: 99%
“…Curiously it was identified in one of the white wines tested (VGB wine from Canary Island). Our data about trans-resveratrol are in agreement with the results from Baptista et al [26,35] that found amounts of this compound in the range of 0.63-5.21 mg L −1 in other Portuguese red wines, including one from Azores Island.…”
Section: Fig 2 (A)supporting
confidence: 93%
“…These two polyphenols have being extensively shown to have several health benefits, namely in the cardiovascular and neurodegenerative protection [32,33]. Gallic acid, also often reported in wine composition [34,35], was identified in all wine samples, while syringic and p-coumaric acid seems to be more specific to white wines. In the same way, m-coumaric acid was only identified in white wines, while rutin was only detected in red wines.…”
Section: Fig 2 (A)mentioning
confidence: 85%
“…If one takes into account that the concentration of Resv in many red wines ranges between 0.5 and 10 mg/ml [18][19][20][21] and that the bioavailability of free Resv in humans is extremely low (1-2% at the most), 22,23) the amount of Resv used in the different assays of the present study was within the concentration range of Resv taken up when drinking one glass of red wine (125 ml) per day. In the case of "-viniferin, such a calculation cannot be made, since data on its bioavailability in humans are not available.…”
Section: Discussionmentioning
confidence: 85%